Susceptibility of Escherichia coli, Salmonella sp. and Clostridium perfringensto organic acids and monolaurin - E. Skrivanova; M. Marounek; V. Benda; P. Brezina (Veterinární Medicína, 2006)
The antimicrobial activity of fatty acids, monolaurin, citric, succinic, fumaric, malic and lactic acid was determined in cultures of two strains of Escherichia coli, three strains of Salmonella sp. and two strains of Clostridium perfringens. Antimicrobial activity was expressed as minimum inhibitory concentration (MIC) that prevented growth and glucose utilization in treated cultures. Caprylic acid was the only acid inhibiting glucose utilization in all cultures. Its MIC varied from 1 to 3 mg/ml. Strains CCM 3954 and CCM 4225 of E. coli were inhibited also by capric acid at 5 mg/ml. Strains CCM 4435T and CNCTC 5459 of Cl. perfringens were inhibited by medium-chain fatty acids (C8 to C14), oleic acid and one strain also by linoleic acid. The minimum MICs were those of lauric and myristic acid (between 0.1 and 0.2 mg/ml). Growth of Cl. perfringens, but not other bacteria, was inhibited also by monoglyceride of lauric acid (MIC = 3 mg/ml), and by citric acid (MIC = 4 mg/ml). Inhibitory effects of other acids were not observed at 5 mg/ml. Caprylic and lauric acid did not influence the K+ permeability of the cytoplasmic membrane in cells of E. coli CCM 4225 and Cl. perfringens CCM 4435T, respectively. In cultures of both strains of E. coli treated with caprylic acid at 5 mg/ml, and in those of Cl. perfringens CCM 4435T treated with lauric acid at 1 mg/ml, or with its monoglyceride at 5 mg/ml, the transmission electron microscopy revealed damage of cytoplasmatic structures. In cells of Cl. perfringens the separation of inner and outer membranes was apparent, the integrity of the outer membrane, however, was maintained. It can be concluded that medium-chain fatty acids are more efficient antimicrobials than other, more polar organic acids tested.